Why theatre matters : urban youth, engagement, and a pedagogy of the real - Gallagher, Kathleen, 1965- (University of Toronto Press, 2014)
What makes young people care about themselves, others, their communities, and their futures? In Why Theatre Matters, Kathleen Gallagher uses the drama classroom as a window into the daily challenges of marginalized youth in Toronto, Boston, Taipei, and Lucknow. An ethnographic study which mixes quantitative and qualitative methodology in an international multi-site project, Why Theatre Matters ties together the issues of urban and arts education through the lens of student engagement. Gallagher's research presents a framework for understanding student involvement at school in the context of students' families and communities, as well as changing social, political, and economic realities around the world. Taking the reader into the classroom through the voices of the students themselves, Gallagher illustrates how creative expression through theatre can act as a rehearsal space for real, material struggles and for democratic participation. Why Theatre Matters is an invigorating challenge to the myths that surround urban youth and an impressive study of theatre's transformative potential.